Role of Serum Alphafetoprotein in Diagnosing Hepatocellular Carcinoma at the Hepatology Unit of A Tertiary Care Hospital - Raha, Aloke Kumar; Sen, Sunanda (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Hepatocellular Carcinoma (HCC) is responsible for a large proportion of cancer deaths in Bangladesh. Alpha-fetoprotein (AFP) is a serum glycoprotein recognized as a marker for HCC, which is used to detect HCC. This study aimed to observe the level of AFP in the diagnosis of patients with HCC. Materials and methods: This cross sectional observational study has been carried out in the Department of Hepatology, Chattogram Medical College Hospital, Chattogram, Bangladesh, from January 2017 to December 2019. A total of 169 patients were enrolled in this research after consent. Patients were admitted to the hospital based on ultrasonographic findings and ultrasonographic guided Fine Needle Aspiration Cytology (FNAC) was done. 19 patients were lost from follow-up and 150 patients had completed the procedure and were finally evaluated. AFP was measured by automated Chemiluminescent immunoassays. Results: The age distribution of the study patients revealed that almost one-fourth (24%) of patients belonged to 51-60 years of age. The mean age was 55.6±16.64 years ranged from 25-80 years. The majority (90%) of patients were male and 15(10%) were female. It was observed that 64(42.7%) patients had HBsAg positive and almost onethird (29.3%) patients had Anti-HCV positive. Mean serum AFP was 8615.3 ±3629.3IU/ml and the range was 5.19-172000 IU/ml.AFP level was normal (<20 IU/ml) in 30 (20%) patients, moderately elevated (20-399 IU/ml) in 99(66%) patients and markedly elevated (>400 IU/ml) in 21 (14%) patients. Mean AFP was found 997.5±1813.8 IU/ml in multifocal HCC, 250.0±157.6 IU/ml in solitary HCC and 57455.7±82995.3 IU/ml in CLD with HCC. The mean AFP is statistically significant in different USG findings. Conclusions: Serum AFP level used alone is sufficient enough for HCC diagnosis majority of patients. But sometimes confirmation by FNAC can be helpful when confused in HCC diagnosis. JCMCTA 2021 ; 32 (1) : 40-43